Peran Ekstrakurikuler Yoga Asana di SMP Negeri 3 Rendang - Eka Yuliani, Ni Komang; Winanti, Ni Putu; Dewi, Ni Wayan Sri Prabawati Kusuma (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2024)
Abstract Extracurricular yoga asana is an activity carried out outside of subject hours as a forum for character development chosen by students which has the benefit of building physical health and concentration. The issues discussed are: What are the forms of extracurricular implementation of yoga asana at SMP Negeri 3 Rendang? What are the efforts to implement extracurricular yoga asana at SMP Negeri 3 Rendang? What is the role of extracurricular yoga asana at SMP Negeri 3 Rendang? The theories used are structural functional theory and role theory. type of qualitative research. Based on the qualitative descriptive analysis, the results obtained are, 1) the form of extracurricular implementation of yoga asana at SMP Negeri 3 Rendang can be seen from the process which includes: Initial stage, core stage, final stage, and post-implementation of extracurricular yoga asana. 2) Efforts to implement extracurricular yoga asana at SMP Negeri 3 Rendang, namely preparing extracurricular facilities and infrastructure for yoga asana and professional instructors in their fields, 3) The role of extracurricular yoga asana at SMP Negeri 3 Rendang, namely increasing students' learning concentration, improving physical health and students' spirituality and improving students' character, the character that is formed is increasing students' religiousness, increasing students' discipline, increasing students' honesty, and increasing students' independence. Keywords: Role, Extracurricular, Yoga Asana